The Influence of the Problem Based Learning Model Assisted by PhET Simulation on Simple Electric Material on Elementary School Students’ Conceptual Understanding - Adjeng Putri Wahyoerie; Zulherman Zulherman (Journal of Educational Sciences, 2026)
The purpose of this study is to ascertain how students' conceptual understanding of fundamental electricity concepts is affected by the Problem Based Learning approach with the help of PhET simulations. This study used a non-equivalent control group design using a quasi-experimental method in a quantitative manner. Fifth-grade primary school pupils from an experimental class and a control class made up the study sample, consisting of 102 students (49 students in the experimental class and 53 students in the control class). Concept Understanding assessments were used to gather research data both before and after teaching. According to the findings, students in the experimental class had an average concept understanding score of 35.20, which was greater than that of the control group (28.17). The Mann-Whitney test was used for hypothesis testing after the normality test revealed that the data were not normally distributed. The Mann-Whitney test results revealed a significance value of 0.000 (<0.05) indicating a significant difference between the two groups and a very substantial effect, as shown by the Cohen’s d value of 2.526 (very large category). These findings imply that Problem Based Learning assisted by PhET Simulation can enhance students' conceptual understanding of simple electricity.